PENGARUH STRESSOR SUHU DAN SALINITAS TERHADAP PERKEMBANGAN EMBRIO IKAN NILEM (Osteochilus hasselti) - Vitas Atmadi Prakoso; Kurniawan Kurniawan (Universitas Nusa Bangsa, 2015)
Effects of Temperature and Salinity as Stressors on Embryo Development of Hard-Lipped Barb (Osteochilus Hasselti) Exposure to environmental stressors on fish is an aspect of concern to researchers because its effects can be detrimental to metabolism, growth, disease resistance, reproductive ability, health, and survival of the fish. Although, according to the researchers that stress can be bad for the fish, but this stress phenomenon remains to be studied more deeply. Based on this information, this paper is made to assess the effects of environmental stressors on fish, especially in hard-lipped barb (Osteochilus hasselti) on the embryonic developmental stages. The data collected comes from the results of research conducted at Institute for Freshwater Aquaculture Research and Development (IFARD), Bogor. This paper discussed about temperature and salinity as environmental stressors related to development of early life stage of hard-lipped barb. Hatching, mortality, and survival rates were the indicators of environmental stressors decisive influence on the development of the embryo. In addition, the observation of embryonic development through the microscope is also used as supporting data. Based on research data, it was concluded that environmental stressors such as temperature and salinity beyond the limits of tolerance could interfere with embryonic development of fish nilem. The stressor temperatures for the embryonic development of hard-lipped barb were 25oC and 31oC, while the salinity stressor for hard-lipped barb embryos was above 5 ppt. The results of this study could be used as reference in fish farming activities of hard-lipped barb to optimize seedling production.Key Words: Osteochilus hasselti, embryo development, environmental stressors, temperature, salinity ABSTRAK Paparan terhadap stressor lingkungan pada ikan merupakan aspek yang menjadi perhatian bagi peneliti karena efeknya dapat merugikan metabolisme, pertumbuhan, ketahanan terhadap penyakit, kemampuan reproduksi, kesehatan, dan kelangsungan hidup ikan. Meskipun menurut para peneliti bahwa stress dapat berakibat buruk bagi ikan, namun fenomena stress ini masih perlu dipelajari lebih dalam lagi. Berdasarkan informasi tersebut, tulisan ini dibuat untuk mengkaji pengaruh stressor lingkungan terhadap ikan, khususnya pada spesies ikan nilem (Osteochilus hasselti) pada fase perkembangan embrio. Data yang dikumpulkan berasal dari hasil penelitian yang dilaksanakan di BPPBAT, Bogor. Jenis stressor lingkungan yang akan dibahas pada tulisan ini yaitu suhu dan salinitas. Derajat penetasan, mortalitas, dan tingkat kelangsungan hidup merupakan indikator penentu pengaruh stressor lingkungan terhadap perkembangan embrio. Selain itu, pengamatan perkembangan embrio melalui mikroskop juga dijadikan sebagai data pendukung. Berdasarkan data penelitian, dapat disimpulkan bahwa stressor lingkungan berupa suhu dan salinitas di luar batas toleransi dapat mengganggu perkembangan embrio ikan nilem. Suhu yang bersifat stressor bagi perkembangan embrio ikan nilem yaitu 25oC dan 31oC, sedangkan stressor salinitas bagi embrio ikan nilem yaitu di atas 5 ppt. Hasil dari studi ini dapat dijadikan sebagai acuan dalam kegiatan budidaya ikan nilem untuk mengoptimalkan produksi benih.Kata Kunci: Osteochilus hasselti, Perkembangan embrio, stressor lingkungan, suhu, salinitas